PRASANGKA DALAM AL-QUR’AN - Bakri, Mubarak (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2018)
Prejudice is one of the causes of horizontal conflict in the society today. Starting from prejudice giving rise to excessive suspicion which led to slander and disharmony between one another. Through this article, the author discusses prejudice in the Koran as a source of solutions to all diseases, including prejudice as a social disease. The author uses thematic interpretations as a method in constructing the Qur'anic insights related to verses examining prejudice by taking the keyword az-zannu. Through this word, it is elaborated in depth the nature of az-zannu and its characteristics in the Qur'an, and how it relates to the az-zannu with its own prejudices. Finally, the author also describes the influence of prejudice in modern society today.